Investigating Student Ideas about Cosmology II: Composition of the Universe - Coble, Kim; Nickerson, Melissa D; Bailey, Janelle M; Trouille, Laura E; Cochran, Geraldine L; Camarillo, Carmen T; Cominsky, Lynn R (Astronomy education review, 2013)
Continuing our work from a previous study (Coble et al. 2013), we examine undergraduates' ideas on the composition of the Universe as they progress through a general education astronomy integrated lecture and laboratory course with a focus on active learning. The study was conducted over five semesters at an urban minority-serving institution. The data collected include individual interviews ("N" = 15) and course artifacts ("N" approximately 60), such as prelab surveys, and midterm and final exam questions in a variety of formats. We find that students easily obtain a superficial knowledge of the origins of the chemical elements and the existence of dark matter and dark energy, which they are generally unaware of pre-instruction. However, they are hindered in their ability to reproduce the argument for the existence of dark matter at least in part because of weaknesses in their graph-reading abilities. (Contains 28 tables, 8 figures, and 4 notes.) [See: Investigating Student Ideas about Cosmology-Part I at EJ1005872; and Part III at EJ1014061.]